The Antiprotozoan Potential of Flavonoids - FOTIE, Jean (Pharmacognosy Reviews)
Flavonoids are a large group of plants secondary metabolites known for their wide range of biological and pharmacological activities including antioxidant, cytotoxic, anticancer, cardioprotective, hepatoprotective, neuroprotective, antibacterial and antimicrobial properties. However, although not always recognized, they also displayed strong antiprotozoan potentials. The purpose of this paper is to provide comprehensive review of the antiprotozoan activities of flavonoids with an emphasis on their antimalarial, antileishmanial, antitrypanosomal and antiamebial properties.
Keywords: Flavonoids; antimalarial; antileishmanial; antitrypanosomal and antiamebial activities